Differentiating the Neuropharmacological Properties of Nicotinic Acetylcholine Receptor-Activating Alkaloids - Alijevic, Omar; Jaka, Oihane; Alzualde, Ainhoa; Maradze, Diana; Xia, Wenhao; Frentzel, Stefan; Gifford, Andrew N.; Peitsch, Manuel C.; Hoeng, Julia; Koshibu, Kyoko (Frontiers in Pharmacology, 2022)
Alkaloids that target nicotinic acetylcholine receptors (nAChR) are of great interest because of the critical role they play in mood and anxiety. However, understanding of the neuropharmacological effects of nicotinic alkaloids, such as cotinine and anatabine, is very limited. In this study, we investigated the neuropharmacological effects of three naturally occurring alkaloids – nicotine, cotinine, and anatabine – in vitro and in vivo. A single injection of nicotine induced anxiolytic-like behavioral features in mice by using the SmartCube® behavioral profiling system, while cotinine and anatabine had no detectable effect. The results were corroborated by using the zebrafish novel tank test (NTT), which showed a profound anxiolytic-like effect induced by multiple doses of nicotine after a single 20-min treatment. When the regulation of dopamine and norepinephrine release – the neurotransmitter systems relevant for anxiety – were examined in vitro, we found that nicotine stimulated the release of both norepinephrine and dopamine, while cotinine and anatabine mainly stimulated the dopamine release. The molecular targets of nicotine were confirmed to be nAChRs with its most potent activities against α4β2 and α6/3β2β3 subtypes in vitro. Anatabine was a weaker agonist for these receptors than nicotine. Cotinine was the least potent nAChR compound, only being able to activate α4β2 and α6/3β2β3 subtypes at high doses and no detectable activities against α3β4 and α7 subtypes at the concentrations tested. The observed effects were unlikely due to the off-target effect, because these alkaloids did not bind or regulate >160 other molecular targets in vitro. Thus, the present results suggest that natural nicotinic alkaloids can induce an anxiolytic-like behavior in nonclinical animal models, potency of which may depend on the activation of various nAChRs and regulation of various neurotransmitter systems. Further investigations would help understand their effects on humans, because non-clinical studies should not be taken as a direct indication for human behavior and nicotine is not risk free.